Removal of Reactive Dyes by Electro Coagulation Process from Aqueous Solution (Journal of Engineering, 2020)
The presence of dyes in wastewater has become a major issue all over the world. The discharge of dyes in the environment is concerned for both toxicological and esthetical reasons. In this study, the removal of dyes from aqueous solution by electrocoagulation using aluminum electrodes as cathode and anode were investigated with the electrocoagulation cell of 1litter. The study included: the impact of various operating parameters on the dyes removal efficiency like pH, NaCl concentration, distance between electrodes, voltage, initial dyes concentration and type of electrodes. The dye (congo red) concentrations were (50, 100, 150, and 200 ppm), stirring speed was 120 rpm at room temperature. pH used was maintained constant. The impact of voltage values was chosen as 6, 10, and 14 Volts. On increasing voltage dyes, removals increased significantly. The higher removal efficiency of dyes (99.9%) was achieved at (30) minutes for (Al/Al) electrodes at pH 6.5-7 and voltage 14 Volts. The results showed that the best amount of sodium chloride was found to be 600 ppm in dyes, voltage of 14 Volts, and best gap between the electrodes as 0.5 cm.